Probing for DNA damage with β-hairpins: Similarities in incision efficiencies of bulky DNA adducts by prokaryotic and human nucleotide excision repair systems in vitro - Liu, Yang (2011)
Nucleotide excision repair (NER) is an important prokaryotic and eukaryotic defense mechanism that removes a large variety of structurally distinct lesions in cellular DNA. While the proteins involved are completely different, the mode of action of these two repair systems is similar, involving a cut-and-patch mechanism in which an oligonucleotide sequence containing the lesion is excised. The prokaryotic and eukaryotic NER damage-recognition factors have common structural features of β-hairpin intrusion between the two DNA strands at the site of the lesion. In the present study, we explored the hypothesis that this common β-hairpin intrusion motif is mirrored in parallel NER incision efficiencies in the two systems. We have utilized human HeLa cell extracts and the prokaryotic UvrABC proteins to determine their relative NER incision efficiencies. We report here comparisons of relative NER efficiencies with a set of stereoisomeric DNA lesions derived from metabolites of benzo[a]pyrene and equine estrogens in different sequence contexts, utilizing 21 samples. We found a general qualitative trend towards similar relative NER incision efficiencies for ~ 65% of these substrates; the other cases deviate mostly by ~ 30% or less from a perfect correlation, although several more distant outliers are also evident. This resemblance is consistent with the hypothesis that lesion recognition through β-hairpin insertion, a common feature of the two systems, is facilitated by local thermodynamic destabilization induced by the lesions in both cases. In the case of the UvrABC system, varying the nature of the UvrC endonuclease, while maintaining the same UvrA/B proteins, can markedly affect the relative incision efficiencies. These observations suggest that, in addition to recognition involving the initial modified duplexes, downstream events involving UvrC can also play a role in distinguishing and processing different lesions in prokaryotic NER.